Determinants of health spending in Algeria Standard Study using ARDL and Boundary Test Models - Mokhtar Hmida; Moustapha Djaballah (Dirassat Journal Economic Issue, 2017)
This paper aims to health policy analysis in Algeria and the status of health expenditure within public spending, with the use of a historical approach since independence have focused on some of the features that characterized the policy spending power in the field of health through research period with dwell ,on the most prominent sources that feed the health expenditure in Algeria and the use of standard study in order to test whether there is the link between the sources of health spending, and have this study concluded that the families sector is an important source recently could affect the health expenditure, along with social security funds, which dropped its role because of deficit.